The loss of that which never was: Evaluating changes to the senior management of the Public Health Agency of Canada. (September 2016) - Fafard, Patrick; Forest, Pierre‐Gerlier
Abstract: In the fall of 2014, the Government of Canada formally split the role of the Chief Public Health Officer (CPHO) into two positions: the CPHO and the President of the Public Health Agency of Canada. Despite concerns raised by the public health community, these changes are consistent with the CPHO's authority. However, the nature of responsible government means that the CPHO cannot simultaneously serve as an independent advocate for policies and programs that might prevent disease and as a senior advisor to the government of the day.